The Effect of Giving Ambon Bananas on Stool Consistency in Toodlers With Diarrhoea in the Gunungpati Semarang Public Health Centre Area - Erni Suprapti; Fitri Wahyuni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Diarrhoea is characterized by an increase in stool frequency (three or more times in 24 hours) with liquid consistency, sometimes accompanied by blood. Common symptoms include abdominal bloating, cramps, nausea, and vomiting. Prolonged diarrhoea in children can lead to dehydration, reduced food intake, weight loss, and potentially failure to thrive. Ambon bananas offer a non-pharmacological approach to managing diarrhoea. This study aimed to determine the effect of Ambon banana consumption on stool consistency in children with diarrhoea. A quasi-experimental, one-group pre-test-post-test design was employed with a purposive sample of 20 children. Results indicated a significant improvement in stool consistency after the intervention (p = 0.000). This study concludes that Ambon bananas can effectively alter stool consistency in children with diarrhoea. Parents are advised to consider incorporating Ambon bananas into the dietary management of diarrhoea in their children.